Pemberdayaan Taman Baca Masyarakat Sebagai Wahana Pendidikan Literasi Anak di Dusun Tibu Kesambik - Dwimaulani, Astrid; Budi Setiawan; Risviana; Anggun Trisnani; Lia Fitriani; Wahyu Aji Saputra; Elvina Dewi Nur Muslimah; Lalu Solihat Mubarrokah; Rosidatul Aini; Samsul Lutfi; Asri Aulia Al Hamdi; Lina Lustina (Politeknik Piksi Ganesha Indonesia, 2025)
The empowerment of the Haqqul Yakin Community Reading Garden (TBM) in Tibu Kesambik Hamlet, Lepak Timur Village, aims to improve children's literacy through the KKN Bina Desa program. This TBM empowerment program employed a three-stage implementation method, namely: preparation stage, implementation stage, and evaluation stage. There were several activities that were carried out such as open book donations, labeling, arranging bookshelves, and literacy assistance in reading and writing. As a result, book donations enrich the reading collection, while labeling and arranging shelves make it easier for children to choose books. Literacy assistance increases children's interest in reading and writing. This program has also succeeded in raising public awareness of the importance of literacy, providing a positive impact on the development of literacy culture in remote areas.